2016
DOI: 10.1080/17569370.2016.1190102
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Taiwanese Female Baby Boomers through their Perceptions of Clothing and Appearance

Abstract: The objectives of this study are twofold: (1) to provide insights and in-depth information regarding the impact of attitudes of female baby boomers in Taiwan toward aging through clothing, and (2) to understand how female baby boomers in Taiwan behave in different contexts in regard to clothing choice, usage and consumption. In order to understand how baby boomers think, feel and behave during the process of aging, clothing was selected as a vehicle to illuminate the complex relationships among various attribu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 53 publications
2
2
0
Order By: Relevance
“…Specifically, they cited enjoyment through window‐shopping, learning new trends, people‐watching, and as a way to break out of the daily routine and stay active. This finding is in line with prior studies (see, for instance, Rahman & Chang, 2018; Wray & Hodges, 2008) that indicate today’s older people are more interested in staying current and active as compared to older people in the past. As one informant claimed:
Well, I love shopping.
…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Specifically, they cited enjoyment through window‐shopping, learning new trends, people‐watching, and as a way to break out of the daily routine and stay active. This finding is in line with prior studies (see, for instance, Rahman & Chang, 2018; Wray & Hodges, 2008) that indicate today’s older people are more interested in staying current and active as compared to older people in the past. As one informant claimed:
Well, I love shopping.
…”
Section: Resultssupporting
confidence: 92%
“…Specifically, they cited enjoyment through window-shopping, learning new trends, people-watching, and as a way to break out of the daily routine and stay active. This finding is in line with prior studies (see, for instance, Rahman & Chang, 2018;Wray & Hodges, 2008) […] I even prefer sometimes, this stuff is weird but it's not weird, I like to shop on a Saturday when everybody else is out. (P13)…”
Section: Hedonic Valuesupporting
confidence: 90%
“…Although gender differences can provide useful information to fashion practitioners and marketers on consumer profiling, gender alone is insufficient to fully elucidate the young consumers' buying motives in China. As previous research [83][84][85] has suggested, demographics alone cannot provide enough information about consumers. This may mean that external, proxy indicators of demographics such as age, may have less explanatory power in regards to clothing choice.…”
Section: Consumer Innovativeness and Domain-specific Innovativeness (Dsi)mentioning
confidence: 89%
“…There have been found that self-reported health status [ 35 ], obesity [ 41 ], and health determinants [ 42 ] differ among the Silent Generation, Baby Boomers, and Generation X. In contrast, research on Baby Boomers and Gen Xers in Taiwan is relatively limited, focusing almost exclusively on retirement [ 43 ] and experiences, preferences, and needs for specific services and products [ 44 46 ]. There is a gap in examining the generational differences in health, lifestyles, and their correlates between the Silent Generation, Baby Boomers, and Generation X of Chinese adults in Taiwan.…”
Section: Introductionmentioning
confidence: 99%